(untitled) (Training and Practice : Journal of Educational Sciences, 2021)
Special education developed for juvenile delinquents is intended to reduce recidivism, assist their entry and reintegration in society as productive citizens, to develop and strengthen delinquents’ self-esteem, sense of responsibility and social utility, close learning gaps, as well as to address the deficiencies in their social, communication, emotional, cultural and learning skills and abilities. Our research aims at providing insight into the perception, awareness of, as well as knowledge and opinions of members of the public related to the education carried out in juvenile correctional facilities. As the social reintegration of former delinquents is a problem affecting the whole society, the public need to be made aware of issues related to juvenile delinquency and correctional institutions, in order to dispel negative perceptions of correctional education and of former juvenile offenders.